A Survey paper on ARM based GPS Controlled Robot for Environment Monitoring using IoT - Bharateesh, C. A.; Kumar, C. S. Pavan; Soujanya, Matam Raghunandana; Ganashree, T. S.; Meharunnisa, S. P. (Journal of ISMAC, 2023)
Environmental screening or monitoring is the process which helps to screen and identify the quality of specific environment. Environmental screening is extensively used in the environmental impact assessments and in situations when human activities can have a devastating effect on the nature. All the screening programs have tactics and agendas which can define the current state of environment or create patterns in environmental constraints. The obtained results are screened, analyzed in various ways and can also be published. Thus, the screening or monitoring task should contribute to put up final use before the process starts. This work elaborates the designing a robot, embedded with sensors to extract atmospheric data from the surroundings. This data is processed and used to monitor the environment, and thereby simultaneously updating the data to the cloud platform namely ThingSpeak. The system can update the sensor data to IoT server at a regular interval of time. The stored data can be used for the future analysis of environmental parameters like in the reduction of overall pollution, conservation of energy and also in providing a complete improved living environment. The above-mentioned robot is intended to use in workplaces where the human intervention is hazardous and sometimes may be fatal to workers.
Keywords: Raspberry Pi; arduino; internet of things; air purifier; smoke sensor; GPS; ARM embedded system